A Review of Lac Production in India during Xi Plan - Jaiswal, A. K.; Singh, J. P. (Indian Forester, 2014)
Analysis of year wise lac production data in India during XI Plan (2007-2008 to 2011-2012) indicated average production by the country to the tune of 16.246 thousand tonnes. The Jharkhand state registered highest average annual production (6.306 thousand tonnes), sharing 38.82 per cent of total lac produced in the country. This is followed by Chhattisgarh (30.21%), Madhya Pradesh (13.66 %), West Bengal (6.97%), Maharashtra (4.96%), Odisha (2.27%), Uttar Pradesh (1.94 %), Assam (0.52%), Andhra Pradesh and Gujarat (0.30% each) and Meghalaya (0.06 %). In respect of state wise growth rate in lac production, the country registered negative growth rate to the tune of 8.38 per cent per annum. Amongst the major lac producing states, Jharkhand and West Bengal recorded positive growth of 12.19 and 9.94 per cent per annum respectively, during this period. Amongst the declining trend state, Madhya Pradesh recorded highest negative growth (-32.41 %) followed by Uttar Pradesh (-29.37%), Chhattisgarh (-26.76%), Maharashtra (-10.62%) and Odisha (-9.92%). The other minor lac producing states namely Assam, Gujarat, Meghalaya also registered declining trend during the period. Strain wise analysis of production data for various states was also carried out in an attempt to identify which type of lac suffered most during this period